2018
DOI: 10.1042/cs20180041
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of CD74 attenuates adipose COX-2-MIF-mediated M1 macrophage polarization and retards obesity-related adipose tissue inflammation and insulin resistance

Abstract: Adipose tissue (AT) inflammation is crucial to the development of obesity-associated insulin resistance. Our aim was to investigate the contribution of cyclooxygenase-2 (COX-2)/macrophage migration inhibitory factor (MIF)-mediated cross-talk between hypertrophic adipocytes and macrophages to the etiology of AT inflammation and the involvement of CD74 using human SGBS adipocytes, THP-1 macrophages and mice fed a high-fat (HF) diet. The and mRNA levels in the adipocytes and stromal vascular cells (SVCs) of white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…CD9 + macrophages are most similar to the CD11c + macrophages and their adoptive transfer into lean mice activates gene expression profiles related to obesity within the AT . Deletion of CD11c, MHC‐II, TNF‐ɑ, CCR2 and CD74 genes before HFD fed in mice causes a marked local and systemic decrease in inflammatory markers and improved glucose tolerance …”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…CD9 + macrophages are most similar to the CD11c + macrophages and their adoptive transfer into lean mice activates gene expression profiles related to obesity within the AT . Deletion of CD11c, MHC‐II, TNF‐ɑ, CCR2 and CD74 genes before HFD fed in mice causes a marked local and systemic decrease in inflammatory markers and improved glucose tolerance …”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…In the early stage of obesity, chemotactic monocyte chemoattractant protein-1 (MCP-1)/C-C chemokine receptor 2 (CCR2) are secreted by hypertrophic adipocyte, in which the cytokines promote the accumulation of macrophage in obese adipose tissue. Studies showed that the secreted MIF can directly facilitate M1 macrophage polarization through CD74 (26,36). In the advanced stage of obesity, M1 macrophage-derived MIF further exacerbates both adipocyte inflammation and macrophage polarization in a positive feedback loop, resulting in the exaggeration of adipose tissue inflammation and insulin resistance (10,26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adipocyte MIF mRNA concentration was also positively associated with adipocytes diameter and independently predicted the peripheral insulin action (23) and the expression of MIF was increased in patients with obesity and diabetes (24). Inhibition or knockdown of MIF or its receptor CD74 could improve the glucose tolerance and insulin resistance, even ameliorate hepatic steatosis induced by HFD (25,26). However, which enzymatic activity of MIF is responsible for affecting HFDinduced inflammation and insulin tolerance in adipose tissues remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of another small‐molecule inhibitor of MIF, ISO‐1, to diabetic db/db mice reduced blood glucose and diabetic nephropathy conditions such as albuminuria, activation of macrophages, and extracellular matrix growth in diabetic kidney . Inhibition of MIF receptor, CD74, using specific shRNA decreased high‐fat‐diet‐induced polarization of macrophages to M1 phenotype and insulin resistance in mice . Additionally, RNAi therapy to inhibit cyclooxygenase‐2 (COX‐2) was found to reduce MIF levels in adipocytes exposed to high fat …”
Section: Cytokines and Therapies That Modulate Their Activitymentioning
confidence: 99%
“…Inhibition of MIF receptor, CD74, using specific shRNA decreased high‐fat‐diet‐induced polarization of macrophages to M1 phenotype and insulin resistance in mice . Additionally, RNAi therapy to inhibit cyclooxygenase‐2 (COX‐2) was found to reduce MIF levels in adipocytes exposed to high fat …”
Section: Cytokines and Therapies That Modulate Their Activitymentioning
confidence: 99%